Latin American lntegration and Synchronization of Business Cycles: The role of Brazil in the integration - Atoche Murrieta, Katherine Lilian (2013)
The integration process in Latin has gane through various stages of advance and retreat. First of aH, the causes that have damaged the integration process follow a continuous pathway is explained by both externa! and interna! factors. The first one refers to the international economic crises that have beaten the Latin American economies. The interna! factors, however, refers to political processes within each country that have prevented the advance of the eco nomic integration. After explaining the process of integration into the XXI Century, we are going to demonstrate that for Latín America there is no a common cycle as a consequence of the economic integration in the regían. At this point we emphasize that one of the important variables for the synchronization of cycles (or existence of a common cycle) is the volume of bilateral trade between the countries. In this part we find statistical evidence that in Latin America there is a low volume of trade. Finally, we focus on Brazil's role in the integration process. Until a few years, Brazil was presented as a candidate to lead the integration process in Latin America. However, in recent years, the international context has made Brazil lost his commercial and political leadership in the region.